Leveraging AI for Collaborative Writing: A Mixed Method Study on Student Experiences using AI Writing Tools - Utami, Silvia; Ariati, Jumerli (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
The immense development of AI, particularly for writing tools, has made it unavoidable for students to become familiar with these technologies. The study investigates using AI writing tools, specifically Canva Magic Write, Quillbot, and Grammarly, in collaborative writing tasks. Eight third-semester students from the English Department at the Faculty of Letters, University of Persada Bunda Indonesia, were selected using a purposeful sampling technique since they have used AI writing tools, including Canva Magic Write, Quillbot, and Grammarly, in Advanced English Grammar and Essay Writing class in the academic 2024-2025 previously. The study employed mixed methods with an explanatory sequential mixed method design, which involved a two-phase data collection process beginning with quantitative data (Questionnaire) and followed by qualitative data (semi-structured interview). The results showed that three AI writing tools - Grammarly, Quillbot, and Canva Magic Write - significantly impact students' collaborative writing experiences. Grammarly improved writing quality, Quillbot enhanced confidence, and Canva Magic Write proved beneficial for idea generation. However, students faced challenges such as restricted access to premium features, issues with source accuracy, irrelevant suggestions, and technical difficulties. Despite these challenges, students expressed satisfaction with Grammarly and Quillbot, while Canva Magic Write received less favorable feedback due to slower performance and outdated sources. The study highlights the importance of understanding students' perceptions and attitudes toward using AI tools for collaborative writing.